2020
DOI: 10.1210/clinem/dgaa519
|View full text |Cite
|
Sign up to set email alerts
|

Low-grade Cortisol Cosecretion Has Limited Impact on ACTH-stimulated AVS Parameters in Primary Aldosteronism

Abstract: Context In primary aldosteronism, cosecretion of cortisol may alter cortisol-derived adrenal venous sampling indices. Objective To identify whether cortisol cosecretion in primary aldosteronism alters adrenal venous sampling parameters and interpretation. Design Retrospective case–control study Setting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 43 publications
2
18
0
Order By: Relevance
“…We restricted studies to those with a sample size ≥10 (to avoid case reports) and written in English. Flow of studies through review and summary of the identified 16 studies are shown in Figure 1A and Table 1 (6,(10)(11)(12)(13)(14)(15)(27)(28)(29)(30)(31)(32)(33)(34)(35).…”
Section: Cortisol Cosecretion In Primary Aldosteronismmentioning
confidence: 99%
See 1 more Smart Citation
“…We restricted studies to those with a sample size ≥10 (to avoid case reports) and written in English. Flow of studies through review and summary of the identified 16 studies are shown in Figure 1A and Table 1 (6,(10)(11)(12)(13)(14)(15)(27)(28)(29)(30)(31)(32)(33)(34)(35).…”
Section: Cortisol Cosecretion In Primary Aldosteronismmentioning
confidence: 99%
“…Based on the findings from AVS in patients with CPA, but without PA, Goupil et al, suggested that autonomous unilateral cortisol hypersecretion could confound the accuracy of AVS by affecting the aldosterone/cortisol ratio in the adrenal vein (i.e., selectivity index, lateralization index, and contralateral suppression index), leading to misdiagnosis and suboptimal management ( 42 ). However, a recent single-center study focusing on PA with mildly elevated cortisol levels (mean serum cortisol levels during the 1-mg DST = 3.3 μg/dl) showed that the rates of cannulation success or lateralization did not differ between PA patients with mild cortisol excess and those without cortisol excess during AVS with ACTH stimulation (blood sample was obtained 1 h after the stimulation) ( 35 ). A multi-center cohort study on this topic would help us to validate their findings and further understand which AVS parameters are useful for the management of PA with cortisol cosecretion.…”
Section: Cortisol Cosecretion In Primary Aldosteronismmentioning
confidence: 99%
“…Several steroid metabolites and metanephrines are potential alternative markers verifying the success of adrenal vein cannulation [ 28 , 29 ]. However, a recent report suggested that an increased plasma cortisol level does not affect the SI under ACTH stimulation in PA patients with subclinical Cushing’s syndrome [ 30 ]. Thus, the SI may be adopted even in patients with cortisol-co-secreting APAs.…”
Section: What Are the Criteria For Successful Avs?mentioning
confidence: 99%
“…As ACS is expected to affect the lateralization diagnosis as well as the success of AVS by altering the cortisol levels in the adrenal veins, the 1 mg Dexamethasone suppression test should be conducted in patients with PA prior to AVS, especially in patients with an apparent adrenal tumor on CT. An increased cortisol level on the tumor side decreases the A/C, while a decreased cortisol level on the contralateral side increases the A/C, which may lead to a decreased LI and an incorrect lateralization diagnosis when using the LI. However, O’Toole et al [ 30 ] reported that mild ACS had a limited impact on AVS parameters when using the A/C with ACTH stimulation. The ratio of the plasma aldosterone concentration (PAC) in the dominant to that in the non-dominant adrenal vein could provide an alternative marker to the LI, although no standard cutoff value has been established for this ratio.…”
Section: What Are the Criteria For Lateralization?mentioning
confidence: 99%
“…Furthermore, ACTH is necessary for patients with contrast allergy who receive steroid treatment before AVS (13). Recently, a study found that ACTH-stimulated AVS might be useful in PA complicated by cortisol co-secretion (14) which has the potential to affect non-ACTH stimulated AVS results (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%